Robust and efficient 3-D numerical model for the hydrodynamic simulation of tsunami wave on land. (December 2020) - Moon, Wei Chek; Puay, How Tion; Lau, Tze Liang
Highlights: Improved accuracy of tsunami wave pressure estimation with 3D numerical model. Temporary moment method adopted to reduce numerical diffusion in VSIAM3 framework for the application in tsunami hydrodynamics problem. Conservative CIP-CSL3 advection scheme and smear-less interface capturing with THINC. Abstract: This study presents the development, refinement, and application of a 3-D multiphase flow model for the simulation of tsunami propagation on land and its hydrodynamic force on a coastal building. The model is based on the Volume/Surface Integrated Average-based Multi-Moment Method (VSIAM3) with improved accuracy by adopting the temporary moment (TM) method to update the non-normal flow variables. A third-order gradient approximation is chosen for the reconstruction of an interpolation profile in the CIP-CLS3 advection solver to further reduce numerical diffusion and suppress numerical oscillation. The moving interface between air–water is captured by using the volume of fluid (VOF) method. The Tangent of Hyperbola for Interface Capturing (THINC) scheme is used to reproduce a sharp and smear-less air–water interface. The model performance improved by as much as 16% in the estimation of impact force on the downstream wall in the dam-break flow benchmarking problem by refining the original VSIAM3 model. The robustness of the model is further demonstrated by the accurate reproduction of tsunami wave propagation speed and its hydrodynamic pressures on a single box-shaped obstacle. The wave-induced pressures on the front face of the obstacle are accurately reproduced, with a maximum of 10% difference compared with the hydraulic experimental results. Thus, the study shows that the overall robustness and hydrodynamic performance of the model can be improved by refining the original model.